EFFECT OF COOKING METHODS ON PROXIMATE COMPOSITION OF ROHUAND CROAKER’SSTEAKS - KAR, S.; CHOWDURY, S.; DORA, K. C.; NATH, S.; SINHA, K.; Pati, K. (Journal of the Inland Fisheries Society of India, 2021)
The effect of six different cooking methods (deep frying at 130 oC, 150 oC and180 oC for 15, 7 and 4.5 min respectively, microwave oven (2450 MHz) for 2.5 mins, boiling and steam-cooking) on proximate composition and energy value of Rohuand Croaker steaks were determined. Significant increase (p<0.05) in crude protein and fat content was observed for treatments T2, T3 and T4. In all treatments, significant lowering (p<0.05) in moisture content was observed that causes increased protein and fat content. Increase in energy value due to frying and microwave cooking was observed, while steaming and boiling recorded lower energy values. Key Words: Proximate composition, energy value, Rohu, Croaker